Investigation of the presence and antinociceptive function of muscarinic acetylcholine receptors in the African naked mole-rat (Heterocephalus glaber) - Jørgensen, Kristine B. (J Comp Physiol A Neuroethol Sens Neural Behav Physiol, 2015)
The present study investigated the cholinergic system in the African naked mole-rat (Heterocephalus glaber) with focus on the muscarinic acetylcholine receptor subtypes M(1) and M(4). The protein sequences for the subtypes m(1–5) of the naked mole-rat were compared to that of the house mouse (Mus musculus) using basic local alignment search tool (BLAST). The presence and function of M(1) and M(4) was investigated in vivo, using the formalin test with the muscarinic receptor agonists xanomeline and VU0152100. Spinal cord tissue from the naked mole-rat was used for receptor saturation binding studies with [(3)H]-N-methylscopolamine. The BLAST test revealed 95 % protein sequence homology showing the naked mole-rat to have the genetic potential to express all five muscarinic acetylcholine receptor subtypes. A significant reduction in pain behavior was demonstrated after administration of 8.4 mg/kg in the formalin test. Administration of 50 mg/kg VU0152100 resulted in a non-significant tendency towards antinociception. The antinociceptive effects were reversed by the muscarinic acetylcholine receptor antagonist atropine. Binding studies indicated presence of muscarinic acetylcholine receptors with a radioligand affinity comparable to that reported in mice. In conclusion, muscarinic acetylcholine receptor subtypes are present in the naked mole-rat and contribute to antinociception in the naked mole-rat.